The Effectiveness of Individual Mental Health Interventions for Depressive, Anxiety and Conduct Disorder Symptoms in School Environment for Adolescents Aged 12–18—A Systematic Review - Karukivi, Johanna; Herrala, Outi; Säteri, Elina; Tornivuori, Anna; Salanterä, Sanna; Aromaa, Minna; Kronström, Kim; Karukivi, Max (Frontiers in Psychiatry, 2021)
Background: Mental health problems are a major health issue for children and adolescents around the world. The school environment allows adolescents to be reached comprehensively and on a low threshold, making it a potential environment for mental health interventions. The aim of this review was to describe interventions delivered by health-care workers in school environment for individual adolescents aged 12-18 with mental health problems and to assess the effectiveness of these interventions. Methods: This systematic review was conducted in adherence with the PRISMA guidelines. Altogether 349 studies were screened and 24 of them were included in full text assessment. Eight studies were included in the qualitative synthesis. Only in three studies the intervention was compared to another intervention or the study setting included a control group. Five of the interventions were based on cognitive-behavioral therapy and three on other approaches. In seven studies, one of the main response variables was based on assessment of depressive symptoms and/or a depressive disorder. The quality of the studies was limited with notable risk for bias for some studies. Results: Based on reported symptom reductions, for most of the interventions, the results were good. Symptom reductions were also typically achieved in a rather low number of sessions (12 or less) supporting the feasibility of these type of interventions in school environment. However, the lack of use of control groups and actual comparisons between the interventions, limit the possibility to draw firm conclusions regarding their effectiveness and thus, the results should be interpreted with caution. Confirming the effectiveness of the studied interventions requires more robust evidence and thus, improving the quality of studies in the school environment is encouraged.